Modeling of a bubble column for CO2 removal by absorption with NaOH - Michelson Johan; Mäki-Arvela Päivi; Rajala Pasi; Hallapuro Markus; Schmid Daniel; Karlström Oskar; Wärnå Johan; Murzin Dmitry Yu (TAYLOR & FRANCIS INC, 2025)
CO2 capture experiments were carried out in a small-scale bubble column reactor using alkaline solutions of sodium hydroxide. The results of the experiments show that a higher NaOH content in the liquid phase and elevated CO2 concentrations in the gas mixture led to a higher CO2 removal efficiency. A mathematical model was developed to describe the CO2 absorption as a function of CO2 gas inlet and OH- concentrations at low CO2 and OH- concentrations. The CO2 uptake at high OH- concentrations (high pH) was accurately predicted by the model, whereas the CO2 uptake at lower OH- concentrations could not be predicted with the same accuracy.